Integrating Scratch-Based Educational Games with Problem-Based Learning to Enhance Students' Conceptual Understanding - Riskawati Riskawati; Khaeruddin Khaeruddin; A. Zaitun A. Zaitun; Kurnia Alda Katrin; Nayla Salsabila; Nurazizah Ramadani; Zakila Intan Asrab; Mardyanto Barumbun (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2026)
This study aimed to describe the implementation of Scratch-based Archery Game media integrated with the Problem Based Learning (PBL) model in teaching momentum and collision concepts in physics. The study employed a one-shot case study design involving 28 students of class XII B at SMAN 14 Gowa, while response data were obtained from 26 students. Data were collected through observation, documentation, and student response questionnaires using a Likert scale, then analyzed descriptively using quantitative and qualitative approaches. The results showed that most PBL syntax stages were successfully implemented through discussion activities, simulation exploration, and game-based problem solving. The learning implementation also indicated the emergence of computational thinking activities, including pattern recognition, abstraction, and algorithmic thinking while students explored momentum and collision simulations. Questionnaire results showed that student responses were in the Good category with a percentage of 78.06%, indicating positive responses toward learning engagement, participation, and the perceived ease of understanding concepts through interactive simulations. The novelty of this study lies in the integration of Scratch-based Archery Game media with the PBL model to support exploratory activities and computational thinking in physics learning. The findings suggest that coding-based media and interactive simulations have the potential to become alternative learning tools for abstract physics concepts that are more contextual, interactive, and relevant to 21st-century learning needs.